(untitled) (Research, Society and Development, 2022)
The text deals with the Lean Office, a theme that is a branch of Lean Manufacturing, a production system originating from the factory of the Toyota company that is very well accepted in the business context. The focus of the study is the balancing of manpower in administrative processes. To achieve this aim, the Yamazumi chart was used. It is a bibliographic study, of a quantitative nature, which has in the case study the mainstay of its methodology. The place where the research practice took place is a commercial organization located in Manaus, northern Brazil. The activities of seven departments were analyzed in order to perceive opportunities for improvement and, consequently, waste reduction in the light of Lean Office principles. After a first round of identification of the company’s processes, here called XYZ Comércio, it was possible to continue with four more balancing rounds and thus reach an optimized level of task distribution and percentage of occupation by processes. The study concludes that the practice of Lean Office using the Yamazumi letter as a tool can represent an opportunity to balance the work effort in order to provide the customer with more quality, efficiency, effectiveness and productivity in the execution of the tasks that make up the day to day. work on the analyzed processes. These are goals that are fully achievable by the will of organizations to achieve more robust results and thus be more competitive in their respective competitive context.